Rhomboids, signalling and cell biology. (9th June 2016) - Freeman, Matthew
Abstract : Here, I take a somewhat personal perspective on signalling control, focusing on the rhomboid-like superfamily of proteins that my group has worked on for almost 20 years. As well as describing some of the key and recent advances, I attempt to draw out signalling themes that emerge. One important message is that the genetic and biochemical perspective on signalling has tended to underplay the importance of cell biology. There is clear evidence that signalling pathways exploit the control of intracellular trafficking, protein quality control and degradation and other cell biological phenomena, as important regulatory opportunities.